Rhododendron retivenium - Tsen, S.; Mohd Yusof, Nur Adillah, M.Y.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Rhododendron retivenium is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 68 km2 and 328.6 km2, respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. It is known from at least three protected areas and no major threat to the population of the species. Hence, it is assessed as Least Concern. Rhododendron retivenium is endemic to Sabah, Malaysia.